Disclosure of Financial Statements: A Study on Mobile Telecommunication Companies in Bangladesh - Neogy , Taposh Kumar (American Journal of Trade and Policy, 2016)
Accounting information produced by AIS through preparing the different financial statements of the selected mobile telecommunication companies is used to meet the needs of interested stakeholders for taking effective decision to serve the different purpose. The selected mobile telecommunication companies follow the provision of IASs/BASs and IFRSs/BFRSs for preparing and presenting the different financial statements. The selected mobile telecommunication companies also follow the Companies Act, 1994, the Securities and Exchange Rules 1987 and other applicable laws in Bangladesh. Accounting Information Systems of the selected mobile telecommunication companies collects stores and disseminates data for the purpose of providing meaningful information to the interested users that assist planning, controlling, coordinating, analyzing and taking effective decision. The general purpose of preparing the different financial statements of the selected mobile telecommunication companies is to provide accounting information to the interested users for taking every effective decision making process. Accurate judgments are impossible unless financial statements are clear and understandable by the interested parties. The study focuses the extent of disclosure scores of the income statement and balance sheet items of the selected mobile telecommunication companies over five years from 2008 to 2012. The results show that the average disclosure scores of income statement and balance sheet items are satisfactory and there is significant difference in disclosure scores of income statement and balance sheet items of the selected mobile telecommunication companies during the period under study. The results also show that most of the respondents reveal that the accounting information produced by AIS of the selected mobile telecommunication companies is moderately adequate and informative and there was significant and non significant difference of opinions among the respondents regarding the adequacy and informativeness of accounting information produced by AIS of the selected mobile telecommunication companies.JEL Classifications Code: M41, F38
Keywords: Disclosure; Financial Statements; Mobile Telecom Companies; Bangladesh